The Teaching New Generation of Students. Millennials in the Hospitality & Tourism Industry - Abdullah, Rahman; Zahari , Harnizam; Adli Zain, Razlan; Nik Mat, Nik Adnan; Derani , Nazarudin; Mohamed Muneer ,; Noor Armia , Radzuan (Advances in Social Sciences Research Journal, 2019)
Millennials is the largest group of segmentation that is still studying and looking forward to join the workforce. Their characteristics, traits, needs and wants, and their ability and talents including their pool of resources available today (technology, internet, mass amount of online information) makes them a group that is going to influence the socioeconomic condition of a nation. The ability of an educator to better understand their condition would be able to alleviate their talent and ability in the right channel while not abusing the previous generation still in the workforce.